2023
DOI: 10.1039/d3cy00102d
|View full text |Cite
|
Sign up to set email alerts
|

Fenton reaction by H2O2 produced on a magnetically recyclable Ag/CuWO4/NiFe2O4 photocatalyst

Abstract: The development of recyclable H2O2-producing photocatalysts with in-situ Fenton-like organic pollutant degradation is currently a topical area of research. This research investigates the visible light photocatalytic formation of H2O2 on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Moreover, adding sacrificial agents also enhanced the in situ photo-Fenton degradation of tetracycline. 26 Liu et al reported H 2 O 2 production on the ZnO/Fe 3 O 4 composite consisting of fine magnetite nanoparticles deposited on ZnO microflowers (Fig. 4a and b).…”
Section: Iron (Fe)-containing Photocatalysts For In Situ Fenton Reactionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, adding sacrificial agents also enhanced the in situ photo-Fenton degradation of tetracycline. 26 Liu et al reported H 2 O 2 production on the ZnO/Fe 3 O 4 composite consisting of fine magnetite nanoparticles deposited on ZnO microflowers (Fig. 4a and b).…”
Section: Iron (Fe)-containing Photocatalysts For In Situ Fenton Reactionmentioning
confidence: 97%
“…This issue can be surmounted if the CB location on the photocatalyst has a stronger affinity to oxygen. 26 Similarly, the molecule to be oxidized should have a higher residence time on the location of the photocatalyst VB.…”
Section: Fundamental Process and General Principles Of Photocatalytic...mentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, a CuWO 4 sample (the detailed synthesis protocol for the bare CuWO 4 is provided in the supplementary information) was also prepared using this precipitation method. 37 Paper PCCP…”
Section: Synthesis Of Nife 2 Omentioning
confidence: 99%
“…15–17 However, the PEC performance of CuWO 4 photoanodes is seriously impeded by the poor charge transfer and slow surface reaction kinetics. 18,19 Up to date, numerous strategies including controlling the morphology, 20 doping with exotic elements, 21 establishing heterojunctions, 22–24 loading with precious metals, 25 and incorporating with surface cocatalysts, 26 have been proposed to improve the PEC performance of CuWO 4 photoanodes. Particularly, constructing heterostructures with a built-in electric field is one of the most effective strategies to accelerate photogenerated charge separation and transfer.…”
Section: Introductionmentioning
confidence: 99%